Facile fabrication of ZnO/N‐doped helical carbon nanotubes composites with enhanced photocatalytic activity toward organic pollutant degradation. (22nd August 2017) - Ma, Shuaishuai; Li, Qing; Cai, Zhilan; Ye, Zhaolian; Zhou, Yuming
Abstract : Novel ZnO/N‐doped helical carbon nanotubes (ZnO/N‐HCNTs) composites were successfully synthesized via a facile chemical precipitation approach at room temperature. The sample was well characterized by X‐ray diffraction (XRD), energy dispersive X‐ray spectroscopy (EDS), transmission electron microscopy (TEM) and ultraviolet–visible diffuse reflectance spectroscopy (UV–vis DRS). The photocatalytic activity was evaluated in the degradation of methylene blue (MB) aqueous solution under UV light irradiation. It is found that ZnO nanoparticles were highly and uniformly anchored on the surface and inner tubes of the N‐HCNTs with size of about 5 nm, and significantly enhanced the photocatalytic activity compared to pure ZnO. The enhanced photocatalytic activity of ZnO/N‐HCNTs composites can be ascribed to the integrative synergistic effect of effective interfacial hybridization between N‐HCNTs and ZnO nanoparticles and the prolonged lifetime of photogenerated electron–hole pairs. Moreover, the ZnO/N‐HCNTs could be easily recycled without any obvious decrease in photocatalytic activity and could be promote their application in the area of environmental remediation. Abstract : Novel ZnO/N‐doped helical carbon nanotubes (ZnO/N‐HCNTs) composites were successfully synthesized via a facile chemical precipitation approach at room temperature. It is found that ZnO nanoparticles were highly and uniformly anchored on the surface and inner tubes of the N‐HCNTs with size of about 5 nm, and significantly enhanced the photocatalytic activity compared to pure ZnO.